A comprehensive overview of the medicinal chemistry of antifungal drugs: perspectives and promise. (6th March 2020) - Howard, Kaitlind C.; Dennis, Emily K.; Watt, David S.; Garneau-Tsodikova, Sylvie
Abstract : The emergence of new fungal pathogens makes the development of new antifungal drugs a medical imperative that in recent years motivates the talents of numerous investigators across the world. Abstract : The emergence of new fungal pathogens makes the development of new antifungal drugs a medical imperative that in recent years motivates the talents of numerous investigators across the world. Understanding not only the structural families of these drugs but also their biological targets provides a rational means for evaluating the merits and selectivity of new agents for fungal pathogens and normal cells. An equally important aspect of modern antifungal drug development takes a balanced look at the problems of drug potency and drug resistance. The future development of new antifungal agents will rest with those who employ synthetic and semisynthetic methodology as well as natural product isolation to tackle these problems and with those who possess a clear understanding of fungal cell architecture and drug resistance mechanisms. This review endeavors to provide an introduction to a growing and increasingly important literature, including coverage of the new developments in medicinal chemistry since 2015, and also endeavors to spark the curiosity of investigators who might enter this fascinatingly complex fungal landscape.